Implementasi Program Kemitraan Dalam Corporate Social Responsibility (CSR) Melalui Pemberdayaan Masyarakat Untuk Mewujudkan Pembangunan Kesejahteraan - Moh Anis; H.Pribanus Wantara; H. Moh Syarif (Serat Acitya, 2022)
This research was about the partnership program of CSR conducted by the state owned entreprise through the economic empowerment of SMEs with the provision of capital to improve the revenue to create prosperity. This study was aimed to analyze the implementation of CSR partnership program. This study used the qualitative approach with documentation type and the documentation technique. The data analysis was done through data collection, data reduction, data display and conclusion. The results of this study stated that the implementation of the partnership program of CSR had a legal basis in the implementation and conducted through partnerships based on some business patterns. The CSR partnership program had the allocations funds from SOEs net income, deposits, administrative services/revenue share/margin, interest on deposits, etc. While recommendation that this research is that The Ministry of SOEs should make the procedures for implementing the partnership program that contains stages in providing funds for potential partnership established partners, implementing organizations and evaluation activities